On Complicity - Ides, Bethany (Radical Teacher, 2023)
Grading can be considered as a knowledge-power technology within a lineage of accountancy, human management, and disciplinarity. This essay explores how I situate my own role as teacher within this legacy. Teaching in active resistance to grading requires foregounding these understandings, both with students and with teaching colleagues. However, asking student to "grade themselves" only further substantiates the grade's viability as either reward or restriction, while also encouraging students to even more deeply internalize its method of control. Collaborative pedagogical strategies promoting relational discourse and reciprocity might make way for learning to occur that is impervious to measurement, but classes organized around principles of mutuality are still the exception, not the norm. Must we become "radically complicit" teachers, as Fred Moten and Stefano Harney suggest, in order to effect instititional change?